DILEMA KELEMBAGAAN FORMAL-INFORMAL MUKIM (Studi Kasus Pengelolaan dan Pemanfaatan Sumberdaya Hutan oleh Pemerintahan Mukim Lambalek dan Panglima Uteun) - , KEMAL PASYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
According to Law No. 11 of 2006 on the Governing of Aceh and Qanun No. 4 of 2003 on Government Mukim, Mukim institution currently has a dual function, which is in the governance area and the tradition area. Policy of Aceh Governmentâs regulates the traditional institutions that can be formed by Mukim to help their duties implementation according to the needs and conditions of its region. Several studies have shown that the Mukim less well able to play in carrying out its duties and functions . In addition, at this time there are also other crucial issues that the state, in this case the central government, does not recognize the authority of traditional leaders in the management and utilization of forest resources despite been supported by formal policy. Itâs shown as a gap between expectation and reality which is then formulated to a few question in this research. The author researched on the Dilemma of Mukim in Formal-Informal Institution (Case Study of Forest Resourceâs Management and Utilization by Government of Mukim Lambalek and Panglima Uteun). This study uses descriptive analysis with a qualitative approach. The process of data analysis according to Miles and Huberman by triangulation of data sources and triangulation theory which is inspiring by Ostrom 's Eight Principles. The results showed that the mechanism of management of forest resources in Mukim Lambalek guided by the values and norms called Adat Uteun. The actors are Imeum Mukim , Panglima Uteun and Keuchik Gampong in Mukim Lambalek. Mechanisms of Adat Uteun normatively regulate people to gathering forest resource intelligently according to the customs rules. However, because of the institutional transformation and people of Mukim who tend to be dynamic, the practical of Adat Uteun are not implemented properly so that led to the collapse of institutions in managing forest resources for the needs of the community . The causes are: (1) historical idealism in formulation of Mukim Government policy